Morphological study of safe fixation region of temporomandibular joint prosthesis in Chinese northeast population with 3-dimensional computed tomographic image. Issue 43 (23rd October 2020) - Zhong, Zhuan; Sun, Jialiang; Yu, Zhentao; Han, Yingying; Kang, Chunyang
Abstract : Abstract: This study aimed to measure temporomandibular joint (TMJ) with 3-dimensional (3D) reconstruction technique in Chinese northeast population, and to clarify the region for fixation and to provide morphological basis for the application of TMJ prosthesis in Chinese setting. Computed tomography (CT) scan and 3D reconstruction were performed with 132 individuals. Structural markers and measurements were further performed with a 3D model of the total TMJ, including the width, thickness and angle of zygomatic arch, the width and height of articular fossa, as well as the area, width, thickness and angle of mandible in the fixation region of the TMJ prosthesis. All the measured indicators values were compared between bilateral sides and gender groups. There was no statistical difference in the measured indicators between the left side and the right side ( P > .05). However, certain parameters, including S, L5, L7, P4, and P5, were significantly different among males and females ( P < .05). In this study, 3D CT image was used to obtain the measurement data of TMJ, which provided data support for the clinical application of TMJ prosthesis in Chinese population.